Dispersion reduction in size of new phase inclusions by changing solve supersaturation - Kulik, T.V.; Shpilinskaya, O.L. (Functional Materials, 2012)
Control operation over a new phase inclusions growth by supersaturation change when it is reducing with time is represented in this work. We have got a solution that defines the low of supersaturation variation with time for maintaining the required law of a new phase growth.